2022
DOI: 10.3390/children9060766
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Health Related Quality of Life among Adolescents—A Systematic Review

Abstract: Health-related quality of life is among global health goals not only in adulthood but also in childhood and adolescence. Being a multi-component construct, health-related quality of life covers various domains, such as physical and psychological wellbeing and social and environmental areas. Bullying might significantly influence those domains especially in adolescence, a period of life when numerous personal and interpersonal transformations are experienced. Therefore, the aim of the current systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
(87 reference statements)
0
15
0
Order By: Relevance
“…To assess the quality of the included studies, the Newcastle–Ottawa Scale (NOS) was used [ 16 , 17 ]. The NOS evaluated three categories—selection, comparability, and exposure/outcome—with a maximum overall score of 9 or 10 points for each study, depending on the study design.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the quality of the included studies, the Newcastle–Ottawa Scale (NOS) was used [ 16 , 17 ]. The NOS evaluated three categories—selection, comparability, and exposure/outcome—with a maximum overall score of 9 or 10 points for each study, depending on the study design.…”
Section: Methodsmentioning
confidence: 99%
“…Studies are classified as: very good quality (9–10 stars), good (7–8 stars), satisfactory (5–6 stars), or unsatisfactory (<5 stars). This scale was originally designed for longitudinal studies but it has been modified to evaluate cross-sectional studies in previous studies [ 13 , 14 ]. We have done an additional adaptation for this study: the point 4 of ‘Selection’ section is referred to the validity of measurement tool.…”
Section: Methodsmentioning
confidence: 99%
“…All of these make adolescence a sensitive period during which adverse experiences can have a lasting impact. If an adolescent experiences rejection by peers, it can negatively impact their health-related quality of life [7]. Bullying may be taking place in a more hidden or disguised way, which can make it difficult to recognize and address [7].…”
Section: Bullying Across Childhood and Adolescencementioning
confidence: 99%
“…In their systematic review which included 12 cross-sectional studies, Dubey et al [7] concluded that bullying significantly reduced the healthrelated quality of life for adolescents.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation